Predator occupancy rates in a thinned ponderosa pine forest, Arizona: A pilot study - Kevin J. Barrett; Elizabeth L. Kalies; Carol L. Chambers (Wildlife Society Bulletin)
Abstract Throughout northern Arizona, USA, forest thinning in ponderosa pine (Pinus ponderosa) forests has become a common practice to reduce the threat of stand‐replacing wildfire and to increase plant and animal diversity across the landscape. To determine how thinning affects predator occurrence, we assessed relationships between predator occupancy and the density of small mammals (prey) across a range of tree stocking levels (basal area of 10–65 m2/ha). Predators were detected using 2 techniques: baited track plates and motion‐sensitive cameras. We sampled 33 sites for 2 weeks each in order to detect presence of predators, and estimated occupancy using occupancy models and multimodel inference. We modeled occupancy rates for gray fox (Urocyon cinereoargenteus), coyote (Canis latrans), and raccoon (Procyon lotor). Our results suggest that thinning may have a positive influence on gray fox and coyote abundance, but a negative influence on raccoon abundance. However, our inability to develop strong models that predicted predator occupancy indicates that higher sample sizes and more habitat covariates are needed. Our simulations indicated that, given our occupancy and detection rates, a sample size of 75 sites would allow us to better model occupancy covariates. Overall, we found that predator occupancy can be assessed at large spatial scales using occupancy approaches, particularly using motion‐sensitive cameras, which were the most time‐ and cost‐efficient of the methods we analyzed. © 2012 The Wildlife Society.